Diversidade produtiva a partir de sistemas agroflorestais: uma experiência vivenciada a partir de uma visita de campo realizada durante o estágio institucional do curso de Agroecologia, UFPA - campus Abaetetuba - SILVA, Ivone Rodrigues da (2023)
This paper aims to report on a field visit, which occurred from the curricular activities of the Institutional Internship and the disciplines of Communication and Rural Extension and Assessment of the Sustainability of Family Agroecosystems, offered to the graduating class of Technology in Agroecology, the Federal University of Pará, Abaetetuba Campus, in the year 2023. The visit took place on a family farmer’s property in the Agroextractive Community Cataiandeua, located 15 km from the municipal seat and its purpose was to understand the importance of integrating different curricular activities in order to enable more inter and multidisciplinary teaching-learning processes, also allowing the construction and exchange between popular and scientific knowledge.